Multilingual use assessment questionnaire: a proposal for assessing language and literacy experience - Aparici, Melina; Rosado, Elisa; Tolchinsky, Liliana (Frontiers in Communication, 2024)
The linguistic profile of multilingual individuals can vary significantly due to diversity in linguistic experience. This poses challenges for language researchers, educators, and clinical practitioners. We developed a Multilingual Use Assessment Questionnaire (MUAQ) to capture the heterogeneous nature of multilinguals profiles integrating three dimensions: self-assessment of language(s) competence, language(s) use for mental operations, and language(s) use in different contexts. The questionnaire was administered to bilingual Catalan/Spanish children and adults across three educational levels: elementary school (year 6), secondary school (year 10), and university level. The application of the MUAQ revealed that Catalan/Spanish bilinguals displayed variations in their selfassessed proficiency based on the type of linguistic activity required by each language. While high bilingual competence was concentrated in oral comprehension, production skills exhibited lower bilingual competence and a strong asymmetry between languages emerged in writing. Also, more pronounced preferences for one language were observed for Thinking and Counting. Whereas Catalan (the language of schooling) was more frequently preferred for Counting, a more multilingual approach was observed for Thinking. A significant heterogeneity was also evident in the language(s) used in different contexts, with each third of the study population demonstrating distinct patterns of linguistic behavior depending on the context. An Exploratory Factor Analysis (EFA) identified two key dimensions (linguistic competence skills and languages involved in mental operations) that accounted for a substantial portion of the variance, while the third dimension (language use in different contexts) bifurcated into situational/communicative vs. personal contexts. These results endorse multidimensional approaches for a comprehensive understanding of multilingualism.